Skeletal Muscle Metastases from Breast Cancer: Two Case Reports - Kim, Young Woo; Seo, Kyung Jin; Lee, Su Lim; Kwon, Ki Wook; Hur, Joon; An, Ho Jung; Ko, Yoon Ho; Kim, Jeong Soo; Won, Hye Sung (Journal of breast cancer, 2013)
The skeletal muscle is an unusual site for metastasis from breast cancer. We present two cases of breast cancer that relapsed as skeletal muscle metastasis without other distant organ metastasis. We performed the core needle biopsy of metastatic sites and confirmed discordance in estrogen receptor, progesterone receptors, and human epidermal growth factor receptor 2 expression between primary breast cancer and skeletal muscle metastases. In the second case, we found the skeletal muscle metastasis through F-18 fluorodeoxyglucose positron emission tomography/computed tomography scans (PET/CT). Intramuscular hot spots on PET/CT scans should be considered as a sign of metastasis even in the absence of abnormalities on computed tomography scans. Our patients received systemic chemotherapy, and showed a partial response. Further studies are needed to determine the prognosis and proper management of isolated skeletal muscle metastasis in breast cancer.